The role of metabolic reprogramming in liver cancer and its clinical perspectives - Lu, Mengxiao; Wu, Yingjie; Xia, MinMing; Zhang, Yixin (Frontiers in Oncology, 2024)
Primary liver cancer (PLC), which includes hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (iCCA), remains a leading cause of cancer-related death worldwide. Chronic liver diseases, such as hepatitis B and C infections and metabolic dysfunction-associated steatotic liver disease (MASLD), are key risk factors for PLC. Metabolic reprogramming, a defining feature of cancer, enables liver cancer cells to adapt to the demands of rapid proliferation and the challenging tumor microenvironment (TME). This manuscript examines the pivotal role of metabolic reprogramming in PLC, with an emphasis on the alterations in glucose, lipid, and amino acid metabolism that drive tumor progression. The Warburg effect, marked by increased glycolysis, facilitates rapid energy production and biosynthesis of cellular components in HCC. Changes in lipid metabolism, including elevated de novo fatty acid synthesis and lipid oxidation, support membrane formation and energy storage essential for cancer cell survival. Amino acid metabolism, particularly glutamine utilization, supplies critical carbon and nitrogen for nucleotide synthesis and maintains redox homeostasis. These metabolic adaptations not only enhance tumor growth and invasion but also reshape the TME, promoting immune escape. Targeting these metabolic pathways presents promising therapeutic opportunities for PLC. This review underscores the interaction between metabolic reprogramming and tumor immunity, suggesting potential metabolic targets for innovative therapeutic strategies. A comprehensive understanding of PLC’s intricate metabolic landscape may lead to more effective treatments and better patient outcomes. Integrating metabolomics, genomics, and proteomics in future research will be vital for identifying precise therapeutic targets and advancing personalized therapies for liver cancer.